Advances and Achievements in In Situ Analysis of Corrosion and Structure–Property Relationship in Mg Alloys - Orlov, D.; Joshi, V. (JOM (1989), 2016)
Every year, the TMS Magnesium Committee carefully selects a special topic in research and development related to magnesium (Mg) representing subjects of high interest from both academic and industrial perspectives, as well as demonstrating major achievements within this area. Following last year's topic on Mg microallying, this year's focus is on in situ methods and associated techniques in their broad definition spanning from laboratory- to large-scale facilities to process monitoring. The applications of in situ techniques have a wide spectrum from the analysis of melts and liquid-solid transitions, to solid-state phenomena during thermomechanical processing and heat treatments, to surface interactions with various environments. Therefore, such works are of significant interest to scientists working in the area of Mg alloy development as well as to a much broader audience from both academia and industry. This interest is primarily caused by challenges in the analysis of a structure-property relationship in Mg alloys, and even a cursory glance of literature reveals a sharp increase of publications relevant to this topic recently.